2022
DOI: 10.1088/1748-9326/ac7ac5
|View full text |Cite
|
Sign up to set email alerts
|

Past and projected climate change impacts on heat-related child mortality in Africa

Abstract: Children (<5 years) are highly vulnerable during hot weather due to their reduced ability to thermoregulate. There has been limited quantification of the burden of climate change on health in sub-Saharan Africa, in part due to a lack of evidence on the impacts of weather extremes on mortality and morbidity. Using a linear threshold model of the relationship between daily temperature and child mortality, we estimated the impact of climate change on annual heat-related child deaths for the current (1995–2020)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…However, there is evidence, not included in this review, that the impact of climate change on children is not evenly distributed, but occurs in LMICs that are already experiencing a higher burden of disease [ 21 ]. A study demonstrated that in Africa, climate change has already doubled the heat-related child mortality compared to what would have been expected without climate change [ 58 ]. There is an obvious mismatch between vulnerability to temperature effects and research effort, which needs to be remediated in future work.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is evidence, not included in this review, that the impact of climate change on children is not evenly distributed, but occurs in LMICs that are already experiencing a higher burden of disease [ 21 ]. A study demonstrated that in Africa, climate change has already doubled the heat-related child mortality compared to what would have been expected without climate change [ 58 ]. There is an obvious mismatch between vulnerability to temperature effects and research effort, which needs to be remediated in future work.…”
Section: Resultsmentioning
confidence: 99%
“…Local strategy of tree planting, construction and restoration of water features, and actions designed to modify behaviour throughout heatwaves in an area with housing prone to overheating and where a high proportion of children live [44] Vanuatu and Australia Support 282 communities through advancing access to knowledge; delivering technical help and equipment to support climate-resilient agriculture and fisheries; and increasing livelihood chances for rural and remote communities [45] As explained before, children are amongst the most vulnerable groups dealing with health-related risks generated by climate change, mainly because of their reduced ability to cope with its related illnesses or because of their limited capacity to thermoregulate [46]. This is because of their developing organ systems, psychological immaturity, or the nature of the activities in which they are involved on a daily basis [35].…”
Section: Bangladeshmentioning
confidence: 99%
“…In addition to the precise quantitative relationship between heat and mortality, a robust future projection of heat-related risks also requires an understanding of the uncertainties of in climate change and variability, as well as changes in population size and age structure. The traditional use of CMIP5/6 global climate models with a limited number of ensemble members may overlook the naturally evolving variability in the climate system 20,23 , which could further lead to an uncertain range of future heat-related mortality burdens from warming. The emerging single-model baseline large ensemble simulations are useful for sampling internal climate variability and its roles in future heat-related mortality change.…”
Section: Introductionmentioning
confidence: 99%